DOZ047.27: Esophageal atresia and polyhydramnios. (24th June 2019) - Arntzen, T; Mikkelsen, A; Haugen, G; Emblem, R
Abstract: Background: Prenatal diagnosis of esophageal atresia (EA) is difficult and the detection rate is only 20–35%. Ultrasound features of EA are nonspecific with polyhydramnios as the most reported finding. Polyhydramnios is reported in approximately 2% of all pregnancies and thus have low specificity. The aim of our retrospective study is to explore perinatal characteristics of EA patients with prenatal suspicion of EA. Methods: Patients with EA born in the periods 1996–2002 and 2011–2017 were included after consent of the parents. Data regarding the pregnancy, birth, and perinatal treatment were obtained from medical records. Results: We registered a total of 124 EA patients: 68 from 1996 to 2002, and 56 from 2011 to 2017. Among the 124 patients, 5(4%) had type Gross A or B, 108(87%) type C, 6(5%) type D, and 5(4%) type E. 73(59%) patients had an associated anomaly. 20/124(16%) patients had a prenatal suspicion of EA, and there were no significant differences between neonates with and without prenatal suspicion of EA in terms of birth weight, gestational age, and prematurity. Patients with prenatal suspicion of EA had more caesarean sections, were more frequently born at regional hospitals, and had more associated anomalies. Polyhydramnios was registered in 70 patients; in 18 of these (90% of all with prenatal diagnosis) a prenatal suspicion of EA had been raised. In 52 EA patients with polyhydramnios, no prenatal statement about anomaly was registered. Four of 5 patients (90%) with type A and B had a prenatal suspicion of EA. Corresponding number for type C was 15/108(14%) and 1/5(20%) with type E. Conclusion: The detection rate for EA is low, and prenatal suspicion of EA implicates a more serious condition with higher morbidity than EA patients born without prenatal suspicion of malformation. Four of five patients without fistula to lower esophagus (type A and B) had a prenatal suspicion of EA, and polyhydramnios is the 'signal sign' for the possible presence of esophageal atresia.